Analysis of The Influence of Social Assistence Hope Family Program on The Benefit of Society (Quality of Education) Study in Lubuk Kertang Village, West Brandan District, North Sumatera - Seri Murni; Analiansyah Analiansyah; Suci Lailatul Sifa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
This study aims to see the effect of satisfaction, service, and the benefits of social assistance services for the Hopeful Family Program. This study uses a quantitative approach with multiple linear regression analysis method. Source of data in this research is primary data by distributing questionnaires to respondents. The population of this study were 175 people and a sample of 65 respondents using purposive sampling technique. The results showed that: a) Partially the variables of satisfaction and public service programs did not have a significant effect on the benefit of the community in terms of the quality of education, while the use of services had a significant effect on the benefit of the community in the quality of education. b) Simultaneously the variables of satisfaction, service programs and service benefits together influence the benefit of society in the quality of education with a P-Value = 0.000 < α 0.05. Based on the R2 test, the effect of the independent variable on the dependent variable was 33.9%, while the remaining 66.1% was influenced by other variables not examined in this study.